Estimulación temprana y su incidencia en la coordinación motriz de los niños y niñas del primer año de educación básica del centro educativo “Ciudad De Babahoyo” parroquia rural de Sevilla, cantón Cascales, provincia de Sucumbíos, año lectivo 2014-2015”. lineamientos alternativos - Peña Pacheco, Becky Lizbeth (2016)
This research refers to: “LA ESTIMULACIÓN TEMPRANA Y SU INCIDENCIA EN LA COORDINACIÓN MOTRIZ DE LOS NIÑOS Y NIÑAS DEL PRIMER AÑO DE EDUCACIÓN BÁSICA DEL CENTRO EDUCATIVO “CIUDAD DE BABAHOYO” PARROQUIA RURAL DE SEVILLA, CANTÓN CASCALES, PROVINCIA DE SUCUMBIOS, AÑO LECTIVO 2014-2015”. LINEAMIENTOS ALTERNATIVOS. It was structured and developed in accordance with Regulation of the current Academic Board at the National University of Loja. The central issue has been raised as impacts the absence of early stimulation and poor performance in motor coordination of children in the first year of basic education. It was established as a general objective: Educate teachers and parents about the importance of early stimulation in motor coordination of children in the first year of basic education. The methods used for the preparation of this research work were: scientific, inductive, deductive, synthetic and statistical model, the same that served effectively help to achieve the proposed goal. The techniques and instruments used were: the survey of teachers First-Year Basic Education School "City of Babahoyo" the purpose of establishing early stimulation activities they perform in the daily work with children and Observation Guide that children of first grade of General Basic Education was applied to evaluate the development of motor coordination. The survey of teachers was reached the following determinations: early stimulation influences the learning process and will be demonstrated early stimulation help the child develop confidence and self esteen, in addition to other motor and learning skills. The results of the observation guide show the following percentages: 53% of children develop the skills of motor coordination which gives an equivalent of very satisfactory, 33% of children develop the skills of motor coordination to giving an equivalent satisfactory 14% fail to develop the skills of motor coordination which gives an equivalent of unsatisfactory, so it is determined that a small percentage of children who need a little more stimulation for proper motor coordination. KEYWORDS Stimulation, skills, coordination, motor skills, body